2020
DOI: 10.3390/nu12102962
|View full text |Cite
|
Sign up to set email alerts
|

The Psycho-Affective Roots of Obesity: Results from a French Study in the General Population

Abstract: The aim of the study was to examine the extent to which obese people differ in their emotionally driven and addictive-like eating behaviors from normal-weight and overweight people. A total of 1142 participants were recruited from a general population, by a web-based cross-sectional survey assessing anxiety/depression (Hospital Anxiety and Depression Scale), emotional eating (Emotional Appetite Questionnaire), food addiction (modified Yale Food Addiction Scale), and intuitive eating (Intuitive Eating Scale-2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Eating in response to emotional factors is acknowledged as a high risk factor for developing overweight, obesity, diabetes and heart disease [ 33 35 ]. In response to the negative emotions, participants with obesity and overweight show less effective coping skills leading them to eat more than normal BMI people [ 36 , 37 ]. It was suggested that 60% or more of individuals with overweight or obesity are emotional eaters [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eating in response to emotional factors is acknowledged as a high risk factor for developing overweight, obesity, diabetes and heart disease [ 33 35 ]. In response to the negative emotions, participants with obesity and overweight show less effective coping skills leading them to eat more than normal BMI people [ 36 , 37 ]. It was suggested that 60% or more of individuals with overweight or obesity are emotional eaters [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This special issue includes eleven studies (four reviews and seven original studies). These seven original studies investigate the factors associated with this phenotype in different contexts: patients seeking treatment for an eating disorder, including anorexia nervosa, bulimia nervosa or binge eating disorder [ 12 , 13 ], patients seeking treatment for obesity (i.e., bariatric surgery candidates) [ 14 ], and non-clinical populations (i.e., persons not directly seeking treatment for these conditions) such as adolescents [ 15 ], female restrained eaters [ 16 ], and persons with weight-related disorders recruited in the general population [ 17 ]. This special issue also present four literature reviews that focus on: neuroimaging of sex/gender differences in obesity, in which FA is prevalent [ 18 ], involvement of the melanocortin system in binge eating, food reward and motivation [ 19 ], association between addictive-like eating behavior and attention-deficit/hyperactivity disorder (ADHD) [ 20 ], and a discussion about the FA concept and its practical implications through four complementary disciplines: addiction medicine, nutrition, health psychology, and behavioral neuroscience [ 21 ].…”
mentioning
confidence: 99%
“…Emotion dysregulation is indeed strongly associated with addictive disorders, and it is now integrated as a core component of addictive disorders treatment. In a large sample of 1142 persons recruited in the general population, Bourdier et al used correlation and mediation analyses to compare the association between anxiety, depression, FA, emotional eating and the difficulty to rely on hunger and satiety cues between persons with versus without obesity [ 17 ]. First, they found associations between depression, anxiety, FA symptoms and the difficulty in relying on hunger and satiety cues across all weight classes.…”
mentioning
confidence: 99%
“…Numerous psychological correlates have been identified as predictors of obesity [ 17 , 18 ]. Many of them are interrelated and influence each other [ 19 , 20 ]. Like its determinants, the consequences of obesity are multifactorial and diverse.…”
Section: Introductionmentioning
confidence: 99%